К проблеме локализации памятников каменного века у с. Червонознаменка (Ивановский район Одесской области) - Пиструил, И.В. (Материалы по археологии Северного Причерноморья, 2011)
The paper investigates different aspects of the problem of localization of Stone Age sites in vicinity of Chervonoznamenka village (Ivanovka district of Odessa region), that were discovered in 1960-s by V.I. Kraskovsky.